Astrocytes in Tauopathies - Reid, Matthew J.; Beltran-Lobo, Paula; Johnson, Louisa; Perez-Nievas, Beatriz Gomez; Noble, Wendy (Frontiers in Neurology, 2020)
Tauopathies are a group of neurodegenerative diseases characterized by the progressive accumulation across the brain of hyperphosphorylated aggregates of the microtubule-associated protein tau that vary in isoform composition, structural conformation and localization. Tau aggregates are most commonly deposited within neurons but can show differential association with astrocytes, depending on the disease. Astrocytes, the most abundant neural cells in the brain, play a major role in synapse and neuronal function, and are a key component of the glymphatic system and blood brain barrier. However, their contribution to tauopathy progression is not fully understood. Here we present a brief overview of the association of tau with astrocytes in tauopathies. We discuss findings that support a role for astrocytes in the uptake and spread of pathological tau, and we describe how alterations to astrocyte phenotype in tauopathies may cause functional alterations that impedes their ability to support neurons and/or cause neurotoxicity. The research reviewed here further highlights the importance of considering non-neuronal cells in neurodegeneration and suggests that astrocyte-directed targets that may have utility for therapeutic intervention in tauopathies.